TRANSFORMASI DIGITAL MANAJEMEN GUDANG MELALUI SISTEM INBOUND-OUTBOUND BERBASIS WEB DENGAN PENDEKATAN AGILE SCRUM - Nurdiana; Faridi; Ryan Zulham Ramadhani (Universitas Muhammadiyah Tangerang, 2026)
Digital transformation in warehouse management has become essential to improve operational efficiency and data accuracy, particularly in inbound and outbound processes. PT Astro Technologies Indonesia still faces challenges in logistics management due to the use of semi-manual spreadsheet-based systems, which may lead to data inaccuracies, delays in updates, and lack of transparency. This study aims to develop a web-based inbound-outbound system as an integrated solution to support warehouse digitalization. The research method employs Agile development with the Scrum framework, enabling iterative and adaptive system development. Data collection was conducted through observation, interviews, literature study, and PIECES analysis. The system was designed using Unified Modeling Language (UML) and implemented using PHP and MySQL. The results indicate that the developed system is capable of managing goods movement in real-time, improving inventory accuracy, and supporting distribution across 25 hubs in the Jabodetabek area. The system also includes role-based access control (RBAC) and automated reporting features in PDF and Excel formats. The implementation of this system significantly enhances operational efficiency, data transparency, and reduces operational errors. Keywords: Digital Transformation, Inbound, Outbound, Agile Scrum, Web-Based System